Differences of Interleukin-6 Serum Levels in Lung Cancer Patients and Healthy Individuals in Medan - Dumasari Siagian; Noni Novisari Soeroso; Bintang Yinke Magdalena Sinaga; Putri C Eyanoer (Jurnal Respirologi Indonesia, 2021)
Background: Interleukin-6 (IL-6) is a pro-inflammatory cytokines involved in the development of lung cancer. However, the association of IL-6 in lung cancer patients remains uncertain. The aim of this study was to analyze the difference of IL-6 serum levels in lung cancer patients and healthy individuals in Medan. Methods: This was a case-control study that included 42 lung cancer patients (case) and 42 healthy individuals (control) which was held in Haji Adam Malik General Hospital Medan. The examinations of IL-6 serum levels were conducted for all subjects using ELISA method. Differences of IL-6 serum levels in lung cancer patients and healthy individuals were analyzed using Spearman Correlation test. Results: The mean serum IL-6 levels in lung cancer patients was 45.99 pg/ml while in healthy individuals was 6.24 pg/ml. There was a significant difference of serum IL-6 levels in the lung cancer group compared to healthy individuals (P=0.0005;r=0.854). Conclusion: There was a statistically significant difference of IL-6 serum levels between lung cancer patients and healthy individuals.